8 A biopsychosocial model of care for children and young people (CYP) with persistent, unexplained, physical symptoms (PUPS). (18th November 2019) - Pales, J; Street, K; Howells, R; Lee, A; Burrows, J; Boyd, A; Bloomfield, T; Palfrey, V
Abstract : Aims: PUPS are common, reported by 10–25% of CYP. 1 Symptoms can lead to poor function, overuse of medical resource and reduced school attendance. Co-morbid mental health problems often go unrecognised. Longer term outcomes include adult chronic physical/mental ill-health, reduced employment, high health/welfare costs. 2 3 We established a pilot multi professional assessment/support service to meet the needs of these CYP. Methods: Weekly multiprofessional meetings including paediatrician, psychiatrist, CAMHS worker, psychologist and education wellbeing advisor (EWA) to discuss cases referred by health professionals. Patient/parent consent given. Outcomes included holistic paediatric assessment, joint appointments (paediatrician and CAMHS worker/psychologist), advice and guidance (A&G) to referrer such as signposting/facilitated referral to community services. Some were offered short-term therapeutic intervention with CAMHS worker/psychologist and/or psychiatric assessment. In all cases clear communication with school was facilitated by EWA who supported school attendance; assisting re-integration and improved attendance/wellbeing at school. Results: Over 18 months we discussed 180 patients: 74 male, 104 female, 2 transgender. Average age 14 years. Common PUPS were musculoskeletal pain, fatigue, headaches, abdominal pain and unexplained episodes. All had reduced school attendance. 111 cases referred by Paediatricians/Allied Health professionals, 56 new GP referrals, 13 presented acutely. 106 were offered paediatric appointments. >50% were discharged with recommendations/advice to primary care/education. 25 had joint appointments. 38 were seen by psychiatrist/CAMHS worker/psychologist for assessment/therapeutic intervention. Remainder received A&G and EWA support. Cost analysis demonstrated average savings of £2600/patient in secondary care. School attendance improved for the majority with reintegration plans and reduction in use of out of school provision with associated cost savings. Referrals to tertiary services for chronic pain/fatigue were reduced and joint working with these services was developed. Linked case examples show significant improvement. Conclusion: Multiprofessional assessment using a biopsychosocial approach to CYP with PUPS leads to better recognition of underlying mental illness, improved short-term functional outcomes, reduced medical costs and improved school attendance. The challenge is securing longer term funding References: Hinton D, Kirk S. Families'and Healthcare Professionals' perceptions of healthcare services for children and young people with medically unexplained symptoms: a narrative review of the literature. Health & social care in the community 2016;24(1):12–26. Campo JV. Annual Research Review: Functional somatic symptoms and associated anxiety and depression – developmental psychopathology in pediatric practice. Journal of Child Psychology and Psychiatry 2012;53:575–592. Bermingham SL, Cohen A, Hague J, Parsonage P. The cost of somatisation among the working-age population in England for the year 2008–2009. Mental Health in Family Medicine 2010;7:71–84.